2012
DOI: 10.1111/j.1464-410x.2012.11144.x
|View full text |Cite
|
Sign up to set email alerts
|

Hexanic lipidosterolic extract of Serenoa repens inhibits the expression of two key inflammatory mediators, MCP‐1/CCL2 and VCAM‐1, in vitro

Abstract: What ' s known on the subject? and What does the study add? Pervasive infl ammatory infi ltrates, mainly composed of chronically activated T cells and monocytes/macrophages, have been observed in benign prostatic hyperplasia (BPH). Permixon ® , a hexanic lipidosterolic extract of Serenoa repens (hexanic LSESr) used to treat urinary dysfunction in BPH patients, has anti-infl ammatory activities. This paper provides new insights into the anti-infl ammatory properties of Permixon ® . We report that hexanic LSESr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 29 publications
1
40
1
1
Order By: Relevance
“…Several experimental studies conducted using the hexanic extract of S. repens showed that this drug is able to block the arachidonic acid cascade by decreasing the production of prostaglandins and leukotrienes and to modify inflammatory status by decreasing B lymphocyte infiltrates and IL-1b and tumor necrosis factor (TNF)-a levels, increasing the expression of antiinflammatory genes, and decreasing the expression of proinflammatory genes [18••]. Moreover, a recent study demonstrated that the hexanic extract of S. repens decreases the production of monocyte chemotactic protein-1 and the expression of vascular cell adhesion molecule-1 in human prostate and vascular cells in an inflammatory environment [22]. However, a single clinical study published in 2003 correlated the significant reduction in B lymphocytes and IL-1b and TNF-a levels with a significant improvement in clinical symptoms in patients treated with hexanic extract of S. repens prior to surgery (TURP or adenomectomy) [23].…”
Section: Drugs With Anti-inflammatory Effectmentioning
confidence: 98%
“…Several experimental studies conducted using the hexanic extract of S. repens showed that this drug is able to block the arachidonic acid cascade by decreasing the production of prostaglandins and leukotrienes and to modify inflammatory status by decreasing B lymphocyte infiltrates and IL-1b and tumor necrosis factor (TNF)-a levels, increasing the expression of antiinflammatory genes, and decreasing the expression of proinflammatory genes [18••]. Moreover, a recent study demonstrated that the hexanic extract of S. repens decreases the production of monocyte chemotactic protein-1 and the expression of vascular cell adhesion molecule-1 in human prostate and vascular cells in an inflammatory environment [22]. However, a single clinical study published in 2003 correlated the significant reduction in B lymphocytes and IL-1b and TNF-a levels with a significant improvement in clinical symptoms in patients treated with hexanic extract of S. repens prior to surgery (TURP or adenomectomy) [23].…”
Section: Drugs With Anti-inflammatory Effectmentioning
confidence: 98%
“…At molecular level, binding to the receptors in the lower urinary tract, including the α1-adrenergic receptors, muscarinic acetylcholine receptors, 1,4-dihyropyridine receptors and vanilloid receptors was observed [28]. In addition, it seems that the anti-inflammatory effects Serenoa repens extracts EFFECTS OF SERENOA REPENS ALCOHOL EXTRACT ON BENIGN PROSTATE HYPERPLASIA are mediated by modulation of the expression of inflammation related-genes, while anti-androgenic effects are primarily due to the inhibition of type 1 and type 2 isoenzymes of 5α-reductase [12,13]. It should be noted that the extraction methods also have an impact on the pharmacological action in BPH and this may be one of the major reasons for studies' inconsistencies [14,29].…”
Section: Discussionmentioning
confidence: 99%
“…The extract of the North American dwarf palm tree Serenoa repens is a phytopharmaceutical product that is most commonly used for the treatment of urological symptoms associated with benign prostatic hyperplasia [10]. Moreover, the commercial preparations of this phytotherapeutic agent are increasingly becoming a treatment option, they have a long history of research and relatively well determined mechanisms of action [11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…[2] reported a signi icant reduction of interleukin 1 and TNFa levels 3 months after Serenoa repens treatment compared with the placebo arm. Recently, Latil et al [3], showed that Serenoa repensinhibits the expression of two" [4].…”
Section: Resultsmentioning
confidence: 99%